Empowering the Bedadung Jember Community in the Upper Watershed Area through the Establishment of a Conservation Village: Pemberdayaan Masyarakat Hulu DAS Bedadung Jember Melalui Pembentukan Kampung Konservasi - Kustiawan Alfarisy, Fariz; Habriantono, Bakhroini; Wagiyana; Suharto (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
The Bedadung River is the largest in Jember Regency and is a water source for the surrounding communities. The Bedadung River, from its upper reaches to its middle and lower parts, is utilized for domestic needs, agriculture and plantations, livestock farming, industry, and tourism. However, despite its significant benefits to the community, the Bedadung River also poses risks, such as floods and droughts. Droughts and floods are recurring disasters that happen every year. These changing conditions are highly dynamic and dependent on the seasons. The disasters have caused considerable losses and are mostly the result of several issues, with a significant portion attributed to climate change. Climate change is marked by changes in land use, such as the population of trees in the upper region. Sucopangepok Village is one of the villages located in the upstream area of the Bedadung River. It is also affected by droughts and floods due to changes in the function of the upstream area. The risk of floods and droughts has motivated the service team to initiate a conservation village. After analyzing the situation, several problems were identified among the service partners, including ecological, social, and economic issues in the upstream area of the Bedadung River. The implementation method of the service includes 1) Tree planting conservation activities; 2) Focus Group Discussions on sustainable agriculture and disaster management; 3) Partner participation in activities; 4) Monitoring and evaluation. The result of the activity is the strengthening of institutions through forming farmer groups, counseling, and guidance on the conservation village program through Focus Group Discussions on the importance of planting perennial crops and monitoring and evaluation of planting activities that have been carried out.